Historical Service Quality Assessment of Malaysia’s World Heritage Site / Hasnawati Haji Guliling and Yuhanis Abdul Aziz - Haji Guliling, Hasnawati; Abdul Aziz, Yuhanis (Faculty of Business and Management ; UiTM Press, 2018)
The tourism sector is experiencing a remarkable constant progress and becoming one of the fastest growing economic sectors globally. In this context, it is interest for the academics and destination marketing organizations to undertake a dedicated study that gives a greater understanding of the concept of satisfaction in enhancing tourists’ loyalty. The purpose of this paper is to discuss the impact of service quality as one of the key antecedents affecting tourists’ satisfaction and loyalty towards selected destinations of the World Heritage Site in Malaysia. To confine the scope of the study, the area of interest focuses on a specific type of city, namely the Heritage City. The historical cities of Melaka and George Town inscribed as UNESCO World Heritage City in Malaysia are chosen in order to gain a comprehensive understanding of the tourists’ attitudes towards heritage city. The sample consists of 450 international and domestic tourists who visited the heritage city. Theoretically, the study contributes to the body of knowledge by emphasizing on key antecedents affecting tourists’ behaviour. Practically, the research findings imply suggestive value to destination marketing planning for Malaysian tourist destinations. At the conclusion, the study makes suggestion of the employment of HISTOQUAL model, which provides a detailed and valuable insight into the service quality assessment of the heritage settings.